Extraction and Analysis of Essential Oil of Cumin - Benrejdal, A.; Dridi, F.; Nabiev, M. (Asian Journal of Chemistry, 2012)
Among the plants belonging to the Umbelliferae family, we were interested in the cumin (Cuminum cyminum) cultivated in Algeria. In this work, we have studied the hydrodistillation process, which showed that in spite of the relatively long duration of the extraction (270 min), we could reach the bearing representing equilibrium. The analysis of essential oil was realized by the method of gas chromatography coupled with the mass spectroscopy (GC/MS). The results allowed to identify the major components which are: the cuminaldehyde and the 1-phenyl-1,2-ethanediol, accompanied with products in small quantity. The results of the physicochemical analyses of essential oil showed that they are in conformity with the A.F.N.O.R norm.